464 Clonal replacement of tumor-infiltrating CD8+ T cells by induction and activation of tumor-residing Batf3-dependent dendritic cells. (10th December 2020) - Oba, Takaaki; Long, Mark; Keler, Tibor; Marsh, Henry; Minderman, Hans; Abrams, Scott; Liu, Song; Ito, Fumito
Abstract : Background: The ability of cancer cells to ensure T-cell exclusion from the tumor microenvironment (TME) is a significant mechanism of resistance to anti-PD-1/PD-L1 therapy. Evidence indicates crucial roles of Batf3-dependent conventional type 1 dendritic cells (cDC1s) for inducing antitumor T-cell immunity. However, strategies to maximize the engagement of cDC1s into such 'immune cold tumors' remain elusive. Using multiple syngeneic orthotopic mouse models of tumors resistant to anti-PD-L1-therapy, we hypothesized that in situ induction and activation of tumor-residing cDC1s overcomes poor T-cell infiltration. Methods: We utilized three mouse non-T cell-inflamed tumor models that are refractory to anti-PD-L1 therapy (AT-3, B16 and 4T1), and evaluated the efficacy of the combinatorial therapeutic regimen, in situ immunomodulation (ISIM) comprised of intratumoral administration of Fms-like tyrosine kinase 3 receptor ligand (Flt3L) to mobilize cDC1s to the TME, local radiotherapy (RT) to promote immunogenic death of cancer cells and maturation of DCs, and peritumoral CD40/toll-like receptor 3 (TLR3) agonists administration to activate antigen-loaded cDC1s for priming and expansion of tumor-specific CD8+ T cells. Results: Intratumoral administration of Flt3L increased the number of CD103+ DCs in the TME, and RT induced upregulation of CD40 and CD86 in the tumor-residing CD103+ DCs. In situ CD40/TLR3 stimulation facilitated trafficking of CD103+ DCs carrying tumor-associated antigens (TAA) to the tumor draining LN (TdLN), and generation of tumor-specific CD8+ T cells in TdLNs, indicating cross-presentation of TAA. Consequently, ISIM triggered infiltration of tumor-specific stem-like Tcf1+CD8+ T cells into the TME, mediated rapid regression of untreated distant and primary tumors, and rendered poorly T cell-infiltrated tumors responsive to PD-L1 blockade in multiple mouse tumor models. Moreover, T-cell receptor (TCR) sequencing of TILs revealed that ISIM facilitated the infiltration of novel clones in the TME. Importantly, serial ISIM further reshaped the TCR repertoires in the TME which had been destined to become resistant to anti-PD-L1 therapy, and rendered tumors continuously responsive to anti-PD-L1 therapy, resulting in durable complete responses and establishment of tumor-specific immunological memory. Conclusions: Taken together, ISIM not only increased CD8+ T-cell infiltration but also reshaped the intratumoral TCR repertoires. These findings provide insights into the utility of an in situ combinatorial immunotherapeutic regimen for overcoming resistance to anti-PD-L1 therapy due to tumor-mediated mechanisms of immune cell exclusion. Acknowledgements: We thank the NIH Tetramer Core Facility (contract HHSN272201300006C) for provision of MHC-I tetramers, This work was supported by National Cancer Institute (NCI) grant P30CA016056 involving the use of Roswell Park's Flow and Image Cytometry, Pathology Network, Bioinformatics, and Mouse Tumor Model Shared Resource. This work was supported by institutional funds from Roswell Park Comprehensive Cancer Center, the Melanoma Research Alliance (F. Ito), Uehara Memorial Foundation (T. Oba), National Cancer Institute (NCI) grant, K08CA197966 (F. Ito), R50CA211108 (H. Minderman), U24CA232979 (S. Liu) and R01CA172105 (S. Abrams).